Histologic Examination of the Heart in the Forensic Autopsy. Issue 3 (September 2018) - Duncanson, Emily R.; Mackey-Bojack, Shannon M.
Histologic examination of the myocardium, valves, and cardiac blood vessels is often as important as the gross examination. The diagnostic features and categories of heart disease are many and varied, possibly more than any other organ. We present a review of the histologic features of forensically important heart disease.